2014 47th Hawaii International Conference on System Sciences 2014
DOI: 10.1109/hicss.2014.207
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Learning in Facebook: Adverse Effects of Individual Preparation

Abstract: Facebook is a social network very popular among University students for purposes of self-presentation. As social networks support the sharing of ideas, can we facilitate collaborative learning in Facebook? We designed a Facebook app that supports scripting of learners' interaction and the construction of arguments in Facebook. In an empirical study with 128 undergraduate teacher trainees, we investigated how individual preparation and argument structuring influences collaborative learning outcomes. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Even though students do initiate posts, most of the posts are initiated by the respective lecturers. This might another motivating factor, as compared to when the participation is graded [15], [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though students do initiate posts, most of the posts are initiated by the respective lecturers. This might another motivating factor, as compared to when the participation is graded [15], [17].…”
Section: Discussionmentioning
confidence: 99%
“…The findings from [14] mentioned that students are generally reluctant to use Facebook as a learning tool, preferring to keep learning out of their private life. There is another study by Judele et al, indicating that grading and participation in Facebook has adverse [15]. Jamil et al, mentioned that the usage of Facebook has no impact on academic grades and should be further investigated for the communication aspects [16].…”
Section: Related Workmentioning
confidence: 99%
“…Lin (1999) concluded that relationships help create social capital. Judele et al (2014) argue that effective collaboration can only occur if social relationships and a sense of community have been built. Cheung (2011) describes the evolution of the subjective norm to engage in Facebook which appears to be repeated within the context of this study.…”
Section: Creation Of the Facebook Groupmentioning
confidence: 99%